2013
DOI: 10.3109/01902148.2013.858196
|View full text |Cite
|
Sign up to set email alerts
|

Temporal determination of lung NO system and COX-2 upregulation following ischemia–reperfusion injury

Abstract: The time-associated involvement of eNOS, iNOS, and COX-2 enzymes during the evolution of IR injury may point to an early reaction of the NOSs system versus the COX-2. Similar patterns of enzymatic activity were previously shown in the context of lung IR injury. This temporal activation may indicate an involvement of eNOS in an early reparative response, and possibly the late-pathological response, mediated by the coinduction of iNOS-COX-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Mercier et al ( 20 ) investigated vessel alterations induced by high flow through the creation of an aortopulmonary shunt and reported increased smooth muscle cell proliferation, but following 1 week of shunt closure, smooth muscle cells demonstrated increased apoptosis without proliferation. Dolkart et al ( 21 ) reported that the rate of apoptosis in the bronchoalveolar lavage peaks at 12 and 48 h following ischemia-reperfusion. When investigating the mechanisms associated with lung ischemia-reperfusion injury in pulmonary thromboembolism, Deng et al ( 22 ) demonstrated that the number of apoptotic pneumocytes had a negative correlation with the ratio of arterial oxygen partial pressure to fractional inspired oxygen, whereas it had a positive correlation with alveolar polymorphonuclear neutrophils in the reperfusion group.…”
Section: Discussionmentioning
confidence: 99%
“…Mercier et al ( 20 ) investigated vessel alterations induced by high flow through the creation of an aortopulmonary shunt and reported increased smooth muscle cell proliferation, but following 1 week of shunt closure, smooth muscle cells demonstrated increased apoptosis without proliferation. Dolkart et al ( 21 ) reported that the rate of apoptosis in the bronchoalveolar lavage peaks at 12 and 48 h following ischemia-reperfusion. When investigating the mechanisms associated with lung ischemia-reperfusion injury in pulmonary thromboembolism, Deng et al ( 22 ) demonstrated that the number of apoptotic pneumocytes had a negative correlation with the ratio of arterial oxygen partial pressure to fractional inspired oxygen, whereas it had a positive correlation with alveolar polymorphonuclear neutrophils in the reperfusion group.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] CPB-induced lung injury is thought to result from lung ischemia, reperfusion after ischemia/reperfusion (I/R) injury, and systemic inflammatory response syndrome. 6,7 Blockage and recovery of circulation in the heart and lungs during CPB can cause endothelial damage, increase vascular permeability, and enhance recruitment or accumulation and activation of platelets and immune cells in the pulmonary circulation. [8][9][10][11] Moreover, incision of the vessels and the artificial materials used in CPB can activate neutrophil granular cells, 12 further causing inflammatory factors to aggregate and damaging the lung tissues.…”
mentioning
confidence: 99%